COMMON GRAMMATICAL ERRORS MADE BY STUDENTS IN WRITING NARRATIVE PARAGRAPH - Restu Damai Laia (Institut Pendidikan Tapanuli Selatan, 2020)
This research aimed at investigating common grammatical errors made by students in writing narrative paragraph. This research was conducted at the English Language Education Study Program of STKIP Nias Selatan. The subject of this research was consisted of 23 students of English Language Education Study Program. The data of this research were collected from students’ paper in writing narrative paragraph. Based on the data analysis, it was found that the students commonly made morphological grammatical errors and syntactic grammatical errors. The morphological grammatical errors consisted of omission of -ed, substitution of simple not-past, misuse of ‘s, and adding unnecessary ‘s. In addition, Syntactic grammatical errors consisted of misuse of pronoun, adding unnecessary be, omission of preposition, misuse of determiner, and adding unnecessary to. Substitution of simple not-past dominated the error made by the students. These research findings are expected to be advantageous for English lecturer to find out the effective strategy to solve the students’ problem